Feminine Endings in The Duchess of Malfi - Ladan Niayesh (Sillages Critiques)
This article takes as its starting point a convention in prosody that stylistically pushes the feminine and femininity to the margin of the poetic line and excludes them from the metrical norm. Extending that principle to the play, it offers a reflection on the way endings are made distinct for female and male protagonists, and thereby paradoxically opens a space for the feminine and femininity within the text, even if that space can only be reached in loss and death.